Interactive Whiteboard and Instant Quiz for Multimedia Classroom Activity - Ary Mazharuddin Shiddiqi; Royyana M. Ijtihadie; Emerson Eridiansyah Z; Baskoro Adi Pratomo; Tohari Ahmad; Waskhito Wibisono (Institut Teknologi Sepuluh Nopember, 2014)
Information and communication technology have become a very strategic aspect in supporting human life. One of the aspects is in education, particularly the use of e-learning system. In the e-learning system, the use of multimedia (such as video conferencing) technology allows users to have an interactive meeting without having to see collocutor directly. In this system, each user communicates by using computer networks, either locally or through the internet. This trend has encouraged developers to create such applications online. However, most of them are paid application and less convenient to use. This research developed an interactive e-learning system with features such as online quiz, whiteboard, video conference and VoIP. In this system, a web based e-learning system with video VoIP provides learning activities by the interaction of both parties that lecturers and students. This system enables the teacher and user to have an interactive conversation and to have quizzes in the middle of a class. This method is aimed to evaluate the students understanding of the materials currently presented. Delay and jitter value of this system increases along with the increase number of users. With the 15 users, the Hypertext Transfer Protocol (HTTP) delay value reaching 32.3672 and 101.6028 ms for the jitter value. Furthermore with 15 users, the Real Time Messaging Protocol (RTMP0 delay value reached 51.8868 ms and 92.0052 ms for the jitter value.